Image Reconstruction Using Modified Hybrid Transform (Journal of Engineering, 2011)
In this paper, an algorithm for reconstruction of a completely lost blocks using ModifiedHybrid Transform. The algorithms examined in this paper do not require a DC estimationmethod or interpolation. The reconstruction achieved using matrix manipulation based onModified Hybrid transform. Also adopted in this paper smart matrix (Detection Matrix) to detectthe missing blocks for the purpose of rebuilding it. We further asses the performance of theModified Hybrid Transform in lost block reconstruction application. Also this paper discussesthe effect of using multiwavelet and 3D Radon in lost block reconstruction.